Longitudinal evidence for immunosenescence and inflammaging in free-living great tits - Těšický, Martin; Krajzingrová, Tereza; Świderská, Zuzana; Syslová, Kamila; Bílková, Barbora; Eliáš, Jiří; Velová, Hana; Svobodová, Jana; Bauerová, Petra; Albrecht, Tomáš; Vinkler, Michal (Experimental gerontology, 2021)
The first-line effector mechanisms of immune defence, including inflammation and oxidative burst, contribute significantly to host-pathogen resistance. Whether these immune responses undergo age-related changes in birds remains unknown. Here, we tracked selected inflammatory parameters in 54 free-living great tits (Parus major) of known age, captured repeatedly over three consecutive years, with the aims to investigate long-term repeatability and age-dependent changes in cellular oxidative burst responsiveness upon in vitro stimulation with bacterial lipopolysaccharide (LPS), and to identify its relationships with leukotriene B4 (LTB4) levels and haematological traits. In addition, we linked these immunological traits to selected physiological markers (antioxidants and oxidative stress markers). LTB4 levels increased with age and we have shown a similar non-significant tendency also for absolute granulocyte counts, indicating propagating chronic inflammation over the bird's lifetime, consistent with the inflammaging hypothesis. In contrast, cellular oxidative burst followed a quadratic trend of dependency on age with a peak in midlife individuals, in line with the immunosenescence hypothesis. Interestingly, LTB4 levels were positively associated with general oxidative damage, but negatively with antioxidant glutathione peroxidase activity, indicating links to redox balance. This longitudinal study demonstrates the contrasting patterns of age-related changes in background and acute markers of pro-inflammatory immunity contributing to immunosenescence in birds and thus provides basis for interpretation of the tested inflammatory markers in cross-cohort datasets.
Keywords: Aging; Longitudinal Studies; lidé; oxidační stres; zánět; Oxidative Stress; Humans; longitudinální studie; imunosenescence; Immunosenescence; Inflammation; stárnutí